Performance evaluation of the Secondary Town Water Supply and Sanitation Project (STWSSP) - Mosharraf, Monzur (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2014.